In vivo Alpha-amylase and Alpha-glucosidase Inhibitory Potentials of Panicum maximum Jacq. (Guinea grass) Leaf Extract on Wister Rats - Enin, Godwin Ndarake; Okokon, Jude Efiom; David, Enobong Mfon; Emmanuel, Saviour Elisha; Ekanem, Esther Michael; Antia, Bassey Sunday (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Panicum maximum Jacq. (Guinea grass) a medicinal plant used traditionally in the treatment of diseases including diabetes was evaluated for its effect on alpha amylase and alpha glucosidase enzymes in vivo. The crude ethanol extracts (150, 300 and 450 mg/kg) of P. maximum were investigated using starch, sucrose, glucose and maltose as substrates and acarbose as reference drug. The leaf extract caused significant (p<0.05) reduction in blood glucose levels of the treated rats with the four substrates used. The findings show that the leaf extract of Panicum maximum has the potentials to inhibit alpha amylase and alpha glucosidase in rats.